A performance evaluation of mobility management and multihop supplying partner strategies for 3D streaming systems over thin mobile devices. (22nd October 2013) - Maamar, Haifa Raja; Boukerche, Azzedine; Petriu, Emil
Summary: The recent advances in technology and mobile computing led to the rapid growth of networked 3D streaming applications. The emerging services can involve augmented reality, virtual environment walkthrough, multiplayer gaming just to mention a few. Because of the limited network bandwidth of the client‐server approach, research works are now turning toward mobile ad hoc networks‐based streaming, where the resources of each peer are used during the streaming service. Peer‐to‐peer technologies are considering the solution to adapt for scalable applications. Yet, supplying partner selection and 3D data delivery are still significant challenges to face because of the dynamic wireless environment that causes link breakages, high packet loss, an adverse impact on the quality of the 3D media, and a low user satisfaction. In this paper, we propose a supplying partner selection technique coupled with a content delivery technique for peer‐to‐peer 3D streaming over thin mobile devices. Our proposed protocol, which we refer to as MULTIPLY, considers multihop suppliers in order to alleviate the load on the server and uses the signal strength measurement to analyze the wireless link when sending back the 3D data. Given the high dynamicity of the network due to the mobility of the users, the streaming can be greatly affected. We therefore study the impact of the mobility on MULTIPLY. The performance evaluation of our protocol obtained using an extensive set of simulation experiments is then reported. Copyright © 2013 John Wiley & Sons, Ltd.